KETERKAITAN EFIKASI DIRI DENGAN KUALITAS HIDUP PADA PASIEN GAGAL GINJAL KRONIS - Halimatuz Zubaidah; Henry Sudiyanto; Fitria Wahyu Ariyanti (MEDICA MAJAPAHIT, 2024)
Patients undergoing hemodialysis cause a lack of control over daily and social life activities, loss of independence, early retirement, and financial pressures. This causes the patient's quality of life to decrease because patients not only face health problems related to chronic kidney disease but also related to lifelong therapy. Self-efficacy is very important for patients with chronic kidney disease undergoing hemodialysis, namely to maintain their survival. The method of this study was correlational using the simple random sampling technique and the number of samples was 78 chronic kidney disease patients in the hemodialysis room at Lavalette Hospital. The analysis technique uses the sperman rho test. The test results using the sperman rho test obtained a value of p <0.05, namely p = 0.005, which means that there is a relationship between self-efficacy and quality of life in patients with chronic kidney disease (CKD) at Lavalette Hospital Malang.